Planning the Production and Consumption of Timber in Sabah, Malaysia - Ahlan, Joseph (1993)
The forest industry is one of the major contributors to the economy of Sabah. Thus, factors influencing timber production and consumption affect the state's future economy and industrial development. This study is undertaken to analyse the past, present and future timber production of Sabah and to estimate future log consumption by the domestic wood-based industries. Recent Sabah forest inventory data and timber yield estimated by FAO were used for the log production projection. Three scenarios corresponding to different assumptions of timber yield and forest management were developed. For log consumption estimation, static and dynamic models were used and tested in five functional forms. Data over 20 years were employed for this estimation. Data on past trends, government and private sector's projections of domestic and import prices and per capita income were used in the forecasting of log consumption.